Contemporary Zambian art, conceptualism and the 'global' art world - Mulenga, Andrew Mukuka (Rhodes University, Faculty of Humanities, Department of Fine Art, 2017)
In Zambia, 'contemporary art' (as a category constructed by the European-dominated international art world), was introduced by the European settler community and continued within its preserve, remaining largely inaccessible to the indigenous community of Africans until Zambia's independence in 1964. This thesis traces the integration of Africans into the contemporary art community and attributes the process, in part, to a small group of artists of European descent who played a significant role in engaging with Zambians, working side by side with them, subsequently influencing their art production and implicitly shaping the ways in which 'Zambian' art 'ought to' look for decades to come. The research traces the early days of contemporary art practice in Zambia to the Lusaka Art Society and Art Centre Foundation that was founded and run by an all-settler group of formally trained artists with a particular inclination towards sculpture and painting. In the wake of the integration however, art production in the formalist manner was further proliferated by the European diplomatic community which would also go as far as dictating artistic subject matter. This thesis argues that the Eurocentric and pre-eminently formalist approach to contemporary art has cost Zambian artists an international presence. I submit that the few instances where contemporary Zambian art practice has penetrated the 'global art' scene or caught the attention of international curators is due to artists adopting more radical conceptual approaches to art production, often creating tensions with local viewers. This thesis also examines conceptualism in contemporary Zambian art practice and examines the inequalities of the 'global art' world. I argue that conceptual art, although not generally accepted on the Zambian art scene, has played a vital role in helping Zambian artists enter the global art world, albeit modestly.
Keywords: Uncatalogued